Operative difficulties in second stage caesarean section: an obstetrician’s nightmare - Kumari, Maya; Patel, Amrita D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: By definition second stage caesarean section are performed in advanced labour at full cervical dilatation and usually after an unsuccessful attempt at vaginal delivery. It is an undesirable situation owing to the difficulties and fetomaternal complications related to it. Methods: This was a prospective observational study conducted at department of obstetrics and gynaecology, B. J. Medical College and Civil Hospital Ahmedabad between April 2022 to March 2023. All the second stage caesarean section performed were included in this study and were analysed in terms of indications, intra-operative difficulties and postoperative complications along with fetal outcome. During this one-year time period there were a total 7867 deliveries. Out of which 2569 were done by caesarean section. Out of total caesarean sections 51 were performed in second stage of labour. This contributes to 0.64% of total deliveries and 1.98% of all caesarean sections. The overall incidence was 0.64%. Results: During the study period there were a total 7867 deliveries. Out of which 2569 were done by caesarean section, out of this 51 were conducted in the second stage of labour. This contributes to 0.64% of total deliveries and 1.98% of all caesarean sections. Out of all indications the most common was non reassuring fetal heart sound. Intra-operative difficulties include extension of uterine incision (11.76%), blood transfusion was required in 19.60% of cases, 19.60% of cases had blood-tinged urine and there was bladder injury in one case. Baby was delivered by Patwardhan and modified Patwardhan method in 27.45% of cases. In post operative period 19.60% of cases were complicated by febrile illness and 11.76% by wound infection. There was total 10 NICU admissions and one perinatal mortality. Conclusions: Caesarean section in second stage of labour is a technically difficult associated with intraoperative maternal complications and adverse neonatal outcome.